The high resistance loop (H-loop) technique used for all-inside arthroscopic knotless suprapectoral biceps tenodesis: A case series - Zhou, Min; Zhou, Chuanhai; Cui, Dedong; Long, Yi; Guo, Jiang; Zheng, Zhenze; Meng, Ke; Zhang, Jinming; Hou, Jingyi; Yang, Rui (Frontiers in Surgery, 2022)
Introduction: Suprapectoral tenodesis is a common technique for the treatment of long head biceps tendon lesions. However, so far, there is no gold standard treatment in all-side arthroscopy. The purpose of the present study is to introduce and evaluate the functional outcomes of an innovative, all-inside arthroscopic high resistance loop (H-loop) technique for long head of biceps (LHB) tenodesis. Method: From September 2020 to March 2021, a series of cases of 32 consecutive patients who received LHB tenodesis using all-inside arthroscopic high resistance loop technique were included in this study. The American Shoulder and Elbow Surgeon Score (ASES), Visual Analog Scale (VAS), Simple Shoulder Test Score (SST), Constant–Murley scores, and University of California at Los Angeles Scoring System (UCLA) were used to evaluate the clinical outcomes of patients in preoperative and final follow-up. Meanwhile, postoperative complications were also observed. Result: 32 patients (14 women and 18 men, average age was 55.72 years) underwent all-inside arthroscopic knotless suprapectoral biceps tenodesis using the H-Loop stitch technique. The mean time of follow-up was 16.16±2.59 months. The ASES, VAS, Constant–Murley, SST, and UCLA scores improved from 51.53±15.78, 5.50±1.55, 57.75±14.68, 5.00±2.76, and 16.06±3.77 preoperatively, to 89.06±7.48, 0.97±0.82, 87.34±5.46, 10.38±1.54, and 31.25±2.59 in the last follow-up, respectively (P < 0.001). During the follow-up, no patients in this study experienced postoperative complications such as infection of the wound, injury of nerves, and hardware failure; no patients required revision after their operation. In addition, none of the patients had cramping or a “Popeye” deformity during follow-up. Conclusion: This article presents an innovative, all-arthroscopic H-loop technique for LHB tenodesis. This technique for LHB tenodesis showed favorable functional and cosmetic outcomes, as well as high satisfaction rates. Due to its simplicity of operation and satisfactory preliminary clinical outcomes, H-loop technique is perhaps another option to choose in all-side arthroscopic LHB tenodesis.